2021
DOI: 10.1111/cts.13079
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of daridorexant, a dual orexin receptor antagonist, are not affected by renal impairment

Abstract: The aim of this study was to evaluate the impact of renal impairment on the pharmacokinetics (PK), safety, and tolerability of daridorexant, a dual orexin receptor antagonist (DORA) intended for the treatment of insomnia. A single-center, open-label study evaluated the PK of daridorexant in patients with severe renal function impairment (SRFI, determined by creatinine clearance using the Cockcroft-Gault equation; n=8) not on dialysis, and in matched control subjects (based on sex, age, and body weight; n=7). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Daridorexant is extensively metabolized, primarily by CYP3A4 (89%) and mostly excreted via faeces (≈ 57%) and urine (≈ 28%), primarily as metabolites [5,16] The pharmacokinetic properties of daridorexant are not clinically significantly affected by age, sex, race, body size [5], or mild to severe renal impairment (Cockcroft-Gault < 30 ml/ min, not on dialysis) [17]. The presence of moderate (Child-Pugh B), but not mild (Child-Pugh A), liver impairment has been shown to prolong the t ½ of daridorexant and thus the maximum dosage recommended in patients with Child-Pugh B impairment is 25 mg no more than once per night [5,18].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Daridorexant is extensively metabolized, primarily by CYP3A4 (89%) and mostly excreted via faeces (≈ 57%) and urine (≈ 28%), primarily as metabolites [5,16] The pharmacokinetic properties of daridorexant are not clinically significantly affected by age, sex, race, body size [5], or mild to severe renal impairment (Cockcroft-Gault < 30 ml/ min, not on dialysis) [17]. The presence of moderate (Child-Pugh B), but not mild (Child-Pugh A), liver impairment has been shown to prolong the t ½ of daridorexant and thus the maximum dosage recommended in patients with Child-Pugh B impairment is 25 mg no more than once per night [5,18].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…No PK analyses were performed from this study but within the clinical pharmacology program of daridorexant, the pharmacokinetics/pharmacodynamics of daridorexant has been evaluated in healthy young and older adults [37,38]. Specific safety aspects, including the modulating effects of intrinsic [51] and extrinsic factors [52][53][54], human abuse potential [44] and effects on driving performance [55] and safety in special populations (subjects with respiratory disease [56,57] and hepatic or renal impairment [58,59]) have also been evaluated. To summarise, daridorexant is quickly absorbed and cleared from the plasma and the distinct pharmacodynamic effects observed are in accordance with the pharmacokinetics, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…93 There has been evidence that the t½ is prolonged in patients with moderate liver failure (Child-Pugh B stage), and the maximum recommended dose in these patients is 25 mg. 94 While there has been no data in patients with severe liver failure and the usage of daridorexant, there has been studies which demonstrated no changes in the pharmacokinetic properties of daridorexant in relation to mild liver failure (Child-Pugh A stage), mild-to-severe renal failure (Cockcroft-Gault < 30 ml/min, not on dialysis), age, sex, ethnicity, or obesity. 94,95 CLINICAL STUDIES: SAFETY AND EFFICACY Symptoms of insomnia have been self-reported in nearly 30% of the general population and can lead to a wide variety of daytime effects such as fatigue, reduced energy, mood alteration, and cognitive difficulties. 96,97 Daridorexant is a generally safe, well-tolerated DORA that has been studied to improve the symptoms of insomnia and mitigate the negative impact it could have on a patient's daily life.…”
Section: Daridorexant Informationmentioning
confidence: 99%